Novel Prognostic Biomarkers of Mucosal Healing in Ulcerative Colitis Patients Treated With Anti-TNF: Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio. Issue 10 (31st March 2020) - Bertani, Lorenzo; Rossari, Federico; Barberio, Brigida; Demarzo, Maria Giulia; Tapete, Gherardo; Albano, Eleonora; Baiano Svizzero, Giovanni; Ceccarelli, Linda; Mumolo, Maria Gloria; Brombin, Chiara; de Bortoli, Nicola; Bellini, Massimo; et al.
Abstract: Background: Anti-tumor necrosis factor drugs (anti-TNFs) are widely used for the treatment of ulcerative colitis (UC). However, many patients experience loss of response during the first year of therapy. An early predictor of clinical remission and mucosal healing is needed. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are markers of subclinical inflammation poorly evaluated in UC patients treated with anti-TNFs. The aim of this multicenter study was to evaluate whether NLR and PLR could be used as prognostic markers of anti-TNF treatment response. Methods: Patients with UC who started anti-TNF treatment in monotherapy were evaluated. Patients with concomitant corticosteroid treatment ≥20 mg were excluded. We calculated NLR, PLR, and fecal calprotectin before treatment and after induction. The values of NLR and PLR were correlated with clinical remission and mucosal healing at the end of follow-up (54 weeks) using the Mann-Whitney U test and then multivariate analysis was conducted. Results: Eighty-eight patients were included. Patients who reached mucosal healing after 54 weeks of therapy displayed lower levels of both baseline NLR and PLR ( P = 0.0001 and P = 0.04, respectively); similar results were obtained at week 8 ( P = 0.0001 and P = 0.001, respectively). Patients who presented with active ulcers at baseline endoscopic evaluation had higher baseline NLR and PLR values compared with those without detected ulcers ( P = 0.002 and P = 0.0007, respectively). Conclusions: BothNLR and PLR showed a promising role as early predictors of therapeutic response to anti-TNF therapy in UC patients. If confirmed in larger studies, classification and regression trees proposed in this article could be useful to guide clinical decisions regarding anti-TNF treatment. Abstract : We found that NLR and PLR at baseline and after the induction of anti-TNF treatment are strongly correlated with mucosal healing. Both NLR and PLR are cheap and easy-to-perform biomarkers that could be used to guide clinical decisions regarding anti-TNF treatment.